THE IMPORTANCE OF LEGISLATION ON PUBLIC CONTROL IN THE FIGHT AGAINST CORRUPTION. - Yusufjonov Hasanjon Alijon ugli (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Corruption is a widespread problem in various aspects of state and community life, which has a negative impact on economic, social and political stability. Public control plays an important role in the fight against corruption. Public control allows citizens and public organizations to monitor, evaluate and influence state bodies and their activities. This article details the importance of public oversight, its role in legislation, and its role in the fight against corruption.